Uspoređenje učinka Zoledronske kiseline protiv Denosumaba na Metabolismu kostiju, Inflammatorijsku odgovornost i imunoglobulina u bolesnika s koštanom metastazom - Zhang, Xian; Tong, Jinfeng; Wang, Zhi; Yang, Hailong (Journal of Medical Biochemistry, 2025)
Background: This study aimed to compare the effects of Zoledronic Acid (ZA) versus Denosumab (DEN) on bone metabolism, inflammatory response, and immunoglobulins in breast cancer (BC) patients with bone metastases. Methods: The potential study population consisted of 163 patients with bone metastases BC admitted from May 2023 to June 2024. Through propensity score matching (PSM), 122 patients were included, with 61 patients in the ZA group (treated with ZA) and 61 patients in the DEN group (treated with DEN). Levels of tartrate-resistant acid phosphatase 5b (TRACP-5b), bone glutamyl protein (BGP), bone alkaline phosphatase (BALP), and 25-hydroxyvitamin D3 (25(OH)D3) were measured before and after treatment. Additionally, bone mineral density (BMD) of the lumbar spine (L1-L4) and hip, as well as levels of inflammatory factors and immunoglobulins, were assessed. Results: After PSM, baseline characteristics were balanced between the ZA and DEN groups (P > 0.05). No significant difference was observed in post-treatment BMD between the two groups (P > 0.05). However, the DEN group showed significantly lower TRACP-5b and BGP levels and notably higher BALP and 25(OH)D3 levels compared to the ZA group (P < 0.05). In contrast, the ZA group exhibited lower levels of inflammatory factors and higher immunoglobulin levels than the DEN group (P < 0.05). Regarding safety, a lower incidence of adverse reactions was determined in the DEN group versus the ZA group (P < 0.05). Conclusion: In the treatment of BC with bone metastases, DEN demonstrated superior benefits for bone metabolism, while ZA showed better regulation of inflammatory response and immune function.